“Anyone not on the list might as well be dead”: Aboriginal Peoples and the Censuses of Canada, 1851–1916 - Hamilton, Michelle (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractThe enumeration of First Nations and Métis peoples in Canada must be considered differently from other ethnic minorities because of their colonial relationship with the state. Over the nineteenth and early twentieth centuries, Aboriginal peoples in Canada became increasingly subject to a separate regulatory body, the Department of Indian Affairs, and legislation such as the Indian Act, both of which affected the information recorded by the census. As the census extended to Canada’s north and west, Indian Affairs officials often acted as census enumerators, and, consequently, its creation of the legal categories of Métis and status Indian blurred the ethnic definitions laid out by the census instructions. Some Aboriginal peoples viewed the census as part of the ongoing process of their nation-to-nation relationship with the British Crown or the Canadian government, but many refused to cooperate with enumerators, seeing them as part of the colonial order which Indian Affairs attempted to impose upon them. Because the public use samples of census data being released by various Canadian universities will result in new social history research, scholars need to understand the ties between colonialism and the enumeration of Aboriginal peoples in order to interpret the data.